Early Treatment of Ruptured Blood Blister-Like Aneurysms of the Internal Carotid Artery With Flow Diverters Using Single Antiplatelet Therapy: A Single-Center Experience With Long-Term Follow-Up - Tanburoglu, Anil; Andic, Cagatay (Frontiers in Neurology, 2021)
Background and Purpose: Blood Blister-like aneurysms (BBAs) of the internal carotid artery (ICA) are rare entities of cerebral aneurysms. FD use in acutely ruptured aneurysms, timing of treatment and antiplatelet regimen are main debate topics in clinical practice when the treatment decision is flow diversion. The aim of this study is to report the safety and efficacy of a single-center FD treatment for ruptured BBAs in the early phase of SAH using the SAPT regimen. Material and Method: This study involved a retrospective analysis of a prospectively collected database. Records of patients admitted to our clinic and treated by endovascular route on ruptured BBA between January 2013 and December 2020 were reviewed. Ruptured supraclinoid ICA BBAs treated with FD devices with SAPT within 48 h from ictus of SAH are included. BBA of atypical anatomic locations, other endovascular techniques performed, and delayed admissions (>48 h) were excluded from the study. Demographic, clinical and angiographic features of patients and aneurysms, FD types and numbers, periprocedural complications, immediate and follow-up angiographic and clinical outcomes were recorded. Results: A total of six patients with ruptured BBAs treated via FDs within 48 h and used SAPT were included in the study. The mean age was 41.6 years (range from 34 to 45 years), and four of six patients were female. All patients were treated within 48 h after ictus, and the mean treatment day was 1.33 days. One patient received ticagrelor, and five patients received prasugrel as SAPT for one year after treatment. No procedure-related death and rebleeding were recorded. One (16.7 %) treatment responsive procedure-related complication occurred (transient ischemia). Overall good outcome rate was 83.3%. One patient died due to pneumonia. The immediate control angiograms showed complete occlusions of BBAs in one patient (16.6%). The complete occlusion rate was 100 % for five survivors at the control angiogram. The median follow-up was 49.5 months. Conclusion: This single-center experience suggests that early treatment (<2 days) within SAH of ruptured BBAs with FDs using SAPT is safe and effective in terms of clinical and radiological long-term outcomes.